Growth and Development of Exchange Traded Funds (ETFs) Market in India (Global Journal of Management and Business Research, 2022)
Exchange Traded Funds ETFs are similar to mutual funds but unlike mutual funds they are listed on an exchange and traded throughout the day similar to stocks ETFs generally have lower expense ratios and certain tax advantages compared to traditional mutual funds and they allow investors to buy and sell shares at intra-day market prices ETFs are one of the most innovative and successful products introduced on exchanges and have grown tremendously over the years The original ETFs were simple providing diversification benefits at a low cost and allowing intra-day trading This study aims at studying the growth and development of Exchange Traded Funds ETFs in India during the last ten years The growth of ETFs is studied by analysing the increase in the Assets Under Management AUM of ETFs and number folios in the gold and non-gold ETF funds in India ETFs are broadly grouped into Gold ETFs and ETFs other than gold
Keywords: exchange traded funds; gold and non gold etfs; indian etf market; equity derivative